Biosynthesis of Modular Ascarosides in C. elegans. (28th March 2017) - Panda, Oishika; Akagi, Allison E.; Artyukhin, Alexander B.; Judkins, Joshua C.; Le, Henry H.; Mahanti, Parag; Cohen, Sarah M.; Sternberg, Paul W.; Schroeder, Frank C.
Abstract: The nematode Caenorhabditis elegans uses simple building blocks from primary metabolism and a strategy of modular assembly to build a great diversity of signaling molecules, the ascarosides, which function as a chemical language in this model organism. In the ascarosides, the dideoxysugar ascarylose serves as a scaffold to which diverse moieties from lipid, amino acid, neurotransmitter, and nucleoside metabolism are attached. However, the mechanisms that underlie the highly specific assembly of ascarosides are not understood. We show that the acyl‐CoA synthetase ACS‐7, which localizes to lysosome‐related organelles, is specifically required for the attachment of different building blocks to the 4′‐position of ascr#9. We further show that mutants lacking lysosome‐related organelles are defective in the production of all 4′‐modified ascarosides, thus identifying the waste disposal system of the cell as a hotspot for ascaroside biosynthesis.